Spectrum of T-DNA integrations for insertional mutagenesis of Histoplasma capsulatum - Kemski, Megan M. (2012)
Agrobacterium-mediated transformation is being increasingly used for insertional mutagenesis of fungi. To better evaluate its effectiveness as a mutagen for the fungal pathogen Histoplasma capsulatum, we analyzed a collection of randomly selected T-DNA insertion mutants. Testing of different T-DNA element vectors engineered for transformation of fungi showed that pBHt2 provides the highest transformation efficiency and the lowest rate of vector backbone carryover. Sixty-eight individual T-DNA integrations were characterized by recovery of T-DNA ends and flanking genomic sequences. The right border end of the T-DNA is largely preserved whereas the left border end is frequently truncated. Analysis of T-DNA insertion sites confirms the lack of any integration hotspots in the Histoplasma genome. Relative to genes, T-DNA integrations show significant bias towards promoter regions at the expense of coding sequences. With consideration for potential promoter interruption and the demonstrated efficacy of intronic insertions, 61% of mapped T-DNA insertions should impair gene expression or function. Mapping of T-DNA flanking sequences demonstrates 67% of T-DNA integrations are integrations at a single chromosomal site and 31% of T-DNA integrations are associated with large-scale chromosomal rearrangements. This characterization of T-DNA insertions in mutants selected without regard to phenotype supports application of Agrobacterium-mediated transformation as an insertional mutagen for genome-based screens and functional discovery of genes in Histoplasma.